Defense budget flexibility and control: how the U.S. and brazilian systems strike a balance between the two - Alves, Luiz Fernando de Queiroz (2022)
A recurrent challenge affecting defense budgeting systems across federalist nations is balancing budget flexibility and legislative control of military appropriations execution. There has been considerable debate over the unique nature of defense expenditure and how it reflects fiscal considerations. While budget revisions are necessary to maintain flexibility due to the broad scope of the defense budget and the handling of unforeseen events, adherence to financial goals and accountability for what was allowed by the legislative impose control over military expenditures, restricting the military’s versatility in carrying out its appropriations. This project offers why balancing flexibility and control is crucial for both parties to achieve their objectives during the budget execution stage. Then, it determines the attributes that indicate an effective control system and adequate budget flexibility. Finally, it contrasts flexibility tools and control activities between the United States and Brazil. This project analyzes constitutional or other legal authority disparities between the legislature, chief executive, military, treasury, and other actors involved in budgeting systems and defense budget implementation to accomplish these goals. The Congressional Budget Office (CBO), Congressional Research Service (CRS), Office of Management and Budget (OMB), the National Treasury of Brazil (STN), the Federal Budget Secretary (SOF), and other reports are reviewed.